Formulation of Business Strategy in EPC Construction Companies in Indonesia - Muhammad Ghaffa Rizky; Dodie Tricahyono (International Journal of Management and Digital Business, 2026)
PT CTM, an Engineering, Procurement, and Construction (EPC) contractor in Indonesia’s electrical infrastructure sector, has experienced declining performance since 2020. This study aims to formulate prioritized restructuring strategies to enhance the company’s competitiveness and performance. Using a qualitative case study design, six internal and external informants were interviewed. Strategic matrices IFE, EFE, IE, SWOT, and QSPM were systematically applied. Findings indicate that PT CTM is in the “Grow and Build” position. Three primary strategies—renewable energy market expansion, project management digitalization, and long-term partnerships with PLN—were prioritized. These strategies provide